Classical approaches and contemporary theoretical models of explaining ethnic entrepreneurship - Vidicki, Vladan D. (Sociološki pregled, 2020)
The subject of this paper is a review and critical analysis of the basic sociological theories of ethnic entrepreneurship. The first part of the paper will refer to the original theories of ethnic entrepreneurship, classified as classical theoretical approaches, while the second part will be dedicated to contemporary theoretical models of ethnic entrepreneurship. In the first case, it seemed justified to choose the term theoretical approaches since within each of the theories the problem was approached from a specific point of view. On the other hand, the term “model” is used as each of them incorporates all the theories that have emerged so far and integrates them into explanatory models of the process of ethnic entrepreneurship.